Shakespeare’s Religious Frontier - Stevenson, Robert. author. aut Link
XII, 97 p.
Keywords: THIS slight volume is addressed not to Shakespearean special ists, but rather to the general public. My chief purpose has been to view Shakespeare's manipulation of his clergy. The last three chapters deal with ancillary problems. Two articles in this collection have already been published - "Shakespeare's Cardinals and Bishops" in The Crozer Quarterry, April, 1950; "Shakespeare's Interest in Harsnet's Declaration" in Publications of the Modern Language Association, September, 1952. I appreciate the Editors' permission to reprint these essays in the present volume. I also thank Professors Gerald Eades Bentley and Lily Bess Campbell for encourage ment and advice during the writing of the first, fifth, and last pieces in this collection. Neither is however to be held re sponsible for any errors discovered by reviewers. All of the essays in this volume except the first were written either at The Folger Shakespeare Library in 1950 or at The Huntington Library in 1952. I thank the directors and staffs of both libraries for their many exceptional kindnesses. Miss Mary Neighbour of Oxford has placed me further in her debt by typing the completed collection.